Efficacy of Lateral Canthoplasty Combined with Transconjuctival Lower Blepharoplasty in Young Asian Patients - Joo Youn Kim; Jung Il Kim; Hyun Gon Choi; Ki Il Uhm; Dong Hyeok Shin (Archives of Aesthetic Plastic Surgery, 2014)
Background The lower eyelid bag associated with an old and tired appearance is not a rare aesthetic problem in young Asian people who have short palpebral fissures and an up-slanting appearance. Many patients want to make their eyes larger, brighter and more youthful at the same time. The purpose of the current study was to determine the feasibility of lateral canthoplasty combined with transconjunctival lower blepharoplasty in minimizing complications and maximizing aesthetic results. Methods From June 2011 to May 2014, 59 patients underwent inferior orbital fat removal and orbital septal resets through transconjunctival approaches and lateral canthoplasty. Simple inferolateral canthotomy incisions were used to provide a sufficient operative field for manipulation of the orbital septum, to lengthen the horizontal palpebral fissures and to lower the lateral canthal angle. Patients were evaluated to identify the presence of postoperative complications and to assess the need for additional operations. Results Most of the patients were satisfied with the aesthetic results during the 2-12-month postoperative follow-up period. There were no recurrences of lower eyelid bulging, postoperative asymmetry, or wound-related complications. Three cases of entropion and two cases of roundness of the lateral canthal angle occurred following the primary operation. However, there were no further complications after secondary operations to correct the tarsal-periosteal fixation position. Conclusions Lateral canthoplasty combined with transconjunctival lower blepharoplasty using simple lateral canthotomy is a safe and effective method for maximizing aesthetic results in young Asian patients.